ANALISA RESIKO PEMBANGUNAN JALAN TOL NUSA DUA-NGURAH RAI-TANJUNG BENOA TERHADAP TSUNAMI - Edwin Hidayat (TATALOKA, 2013)
The construction of Nusa Dua – Ngurah Rai – Benoa Toll Road in coastal area which has vulnerability of tsunami so for measure the level of vulnerability use the Building TsunamiVulnerability (BTV) from Omira et al (2009), Tsunami Matrix from Sengaji and Nababan (2009),and Coastal Vulnerability Indeks (CVI) by Kumar et al (2010). The result of BTV is 30%, this value included in the class risk D1 which has meaning slight no structural damage. Then with the result showed the value is 4 and include in the class risk 4 which the meaning is high risk. Lastly,measuring with CVI model the result is 16,53 this included in the class risk moderate. We had different results, it is because the parameter and the coefficient value were calculated also different. Furthermore, the parameters tsunami run-up and the type of building materials are parameters which need to be most consider, these parameters are the most dominant factor. It can be concluded that the Nusa Dua - Ngurah Rai - Benoa toll road has vulnerability to Tsunami.Thus, we must preparing the mitigation or adaptation plan, such as, evacuation routes plan, if forece majeur happened.